Three-layer wave-absorbing structure and preparation method thereof

By designing a three-layer structure in the absorbing material and using nanographite as the transition layer of wave impedance, the problem of insufficient absorption performance in the middle frequency band of existing absorbing materials is solved, and a wider absorption frequency band and higher electromagnetic loss performance are achieved.

CN119653755AActive Publication Date: 2025-03-18CHINA ACAD OF AEROSPACE AERODYNAMICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411963082.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The absorption performance of existing wave absorbing materials in the medium frequency band cannot achieve the expected effect, mainly due to the poor wave impedance matching of the material interface.

Method used

A three-layer absorbing structure is designed, including loss dielectric layers A, B and C. By adding nanographite as a transition layer of wave impedance to the intermediate layer, the wave impedance is reasonably gradual, thereby broadening the effective absorbing bandwidth.

Benefits of technology

Through the design of the three-layer structure, the electromagnetic loss performance of the medium frequency band is improved, and the reflection loss value is better than that of the double-layer absorbing materials, effectively widening the absorbing frequency band.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653755A_ABST
    Figure CN119653755A_ABST
Patent Text Reader

Abstract

The invention provides a three-layer wave-absorbing structure and a preparation method thereof. The three-layer wave-absorbing structure comprises a loss dielectric layer A, a loss dielectric layer B and a loss dielectric layer C, the loss dielectric layer A is used as a surface layer, a base material is polylactic acid, and a filler is spherical carbonyl iron; the loss dielectric layer B is used as a middle layer, a base material is polylactic acid, and a filler is nano-graphite; the loss dielectric layer C is used as a bottom layer, the base material is polylactic acid, and the filler is nano carbon particles. According to the three-layer wave-absorbing structure, the wave impedance is sequentially reduced from the surface of the loss dielectric layer A to the interface between the loss dielectric layers, and the wave impedance of the surface of the structure is close to the wave impedance of a free space, so that most of electromagnetic waves enter the material; the added middle dielectric loss layer plays a role in transition of wave impedance, so that the wave impedance is reasonably and gradually changed, and the effective wave-absorbing bandwidth is widened; the reflection loss value in the middle-frequency band is superior to that of a double-layer wave-absorbing material, and the electromagnetic loss performance in the middle-frequency band can be improved through the design of the three-layer structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing structures, and in particular relates to a three-layer wave absorbing structure and a preparation method thereof. Background Art

[0002] Absorbing materials are an important means to achieve stealth technology. The existing absorbing coatings are applicable to a narrow frequency band. The effective absorbing frequency band can be expanded through the stacking design of absorbing materials, but due to the poor wave impedance matching of the material interface in the mid-frequency band, the absorbing performance in the mid-frequency band (4~8 GHz) cannot reach the expected effect. In the design of multi-layer absorbing materials, the materials are arranged from large to small according to their intrinsic impedance as much as possible. Therefore, according to the electromagnetic properties of different absorbing materials, a transition layer with impedance gradient is placed between the surface and bottom layers of the materials. Through the combined design of multi-layer absorbing materials, the wave impedance matching of the materials is further improved, and a better broadband absorbing effect is achieved. Summary of the invention

[0003] In order to overcome the deficiencies in the prior art, the inventors have conducted intensive research and provided a three-layer absorbing structure and a preparation method thereof. On the basis of the design of a double-layer absorbing material, an intermediate layer is added as a transition layer of wave impedance to form a three-layer absorbing structure, so that the wave impedance changes reasonably gradually, further broadens the effective absorbing bandwidth, and improves the electromagnetic loss performance in the mid-frequency band.

[0004] The technical solution provided by the present invention is as follows: In a first aspect, a three-layer absorbing structure includes a lossy dielectric layer A, a lossy dielectric layer B, and a lossy dielectric layer C; The lossy dielectric layer A is used as the surface layer, the base material is polylactic acid, and the filler is spherical carbonyl iron; The lossy dielectric layer B is used as the middle layer, the base material is polylactic acid, and the filler is nanographite; The lossy dielectric layer C is used as the bottom layer, the matrix material is polylactic acid, and the filler is nano-carbon particles.

[0005] In combination with the first aspect, the mass fraction of carbonyl iron in the lossy dielectric layer A is 40% to 70%, and the mass fraction of polylactic acid is 30% to 60%.

[0006] In combination with the first aspect, the mass fraction of nanographite in the lossy dielectric layer B is 10% to 30%, and the mass fraction of polylactic acid is 70% to 90%.

[0007] In combination with the first aspect, the mass fraction of the nano-carbon particles in the lossy dielectric layer C is 10% to 30%, and the mass fraction of the polylactic acid is 70% to 90%.

[0008] In combination with the first aspect, the thickness of the three-layer absorbing structure is 3-5 mm, the thickness of the lossy dielectric layer A is 1-3 mm, the thickness of the lossy dielectric layer B is 1-3 mm, and the thickness of the lossy dielectric layer C is 1-3 mm.

[0009] In a second aspect, a method for preparing a three-layer absorbing structure comprises the following steps: Carbonyl iron and polylactic acid are used to prepare carbonyl iron polylactic acid composite wire; Nano-graphite and polylactic acid are used to prepare nano-graphite polylactic acid composite wires; Nanocarbon particles and polylactic acid are used to prepare nanocarbon particle polylactic acid composite wires; A lossy dielectric layer C is formed by a fused deposition molding process using nano-carbon particle polylactic acid composite wire; a lossy dielectric layer B is formed by a fused deposition molding process using nano-graphite polylactic acid composite wire on the lossy dielectric layer C; a lossy dielectric layer A is formed by a fused deposition molding process using carbonyl iron polylactic acid composite wire on the lossy dielectric layer B, thereby obtaining a three-layer absorbing structure.

[0010] A three-layer absorbing structure and a preparation method thereof provided by the present invention have the following beneficial effects: (1) The present invention provides a three-layer absorbing structure and a preparation method thereof, wherein a lossy dielectric layer A is used as the surface layer, the matrix material is polylactic acid, and the filler is spherical carbonyl iron; a lossy dielectric layer B is used as the middle layer, the matrix material is polylactic acid, and the filler is nanographite; and a lossy dielectric layer C is used as the bottom layer, the matrix material is polylactic acid, and the filler is nanocarbon particles. In the three-layer absorbing structure of the present invention, the wave impedance decreases successively from the surface of the lossy dielectric layer A to the interface between the lossy dielectric layers, and the wave impedance of the surface of the structure is close to the wave impedance of free space, so that most of the electromagnetic waves enter the interior of the material; the added intermediate dielectric loss layer plays a transitional role in the wave impedance, so that the wave impedance changes reasonably gradually, and the effective absorbing bandwidth is widened; the reflection loss value in the mid-frequency band is better than that of the double-layer absorbing material, and the design of the three-layer structure can improve the electromagnetic loss performance in the mid-frequency band.

[0011] (2) The present invention provides a three-layer absorbing structure and a preparation method thereof. The composite wire used in the molten deposition molding process is obtained by a two-step melt blending preparation process, so that the mass ratio and dispersibility of the absorber are significantly improved, thereby realizing the preparation of absorbing composite wires with high electromagnetic loss performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a schematic diagram of a three-layer wave absorbing structure; Figure 2 The wave absorption performance analysis of the three-layer structure of Example 1, which has a surface layer of 1 mm (CI-60 / PLA), a middle layer of 1 mm (NGP-10 / PLA), and a bottom layer of 3 mm (NPC-20 / PLA); Figure 3 The wave absorption performance analysis of the three-layer structure of Example 2, which has a surface layer of 1 mm (CI-60 / PLA), a middle layer of 2 mm (NGP-10 / PLA), and a bottom layer of 2 mm (NPC-20 / PLA); Figure 4 This is an analysis of the wave absorption performance of the double-layer structure of comparative example 1, with a surface layer of 1 mm (CI-60 / PLA) and a bottom layer of 4 mm (NPC-20 / PLA). DETAILED DESCRIPTION

[0013] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.

[0014] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0015] The present invention provides a three-layer absorbing structure, such as Figure 1 As shown, it includes a lossy dielectric layer A, a lossy dielectric layer B and a lossy dielectric layer C; The lossy dielectric layer A is used as the surface layer, the base material is polylactic acid (PLA), and the filler is spherical carbonyl iron (CI); The lossy dielectric layer B is used as the middle layer, the matrix material is polylactic acid, and the filler is nanographite (NGP); The lossy dielectric layer C is used as the bottom layer, the matrix material is polylactic acid, and the filler is nanocarbon particles (NPC); The lossy dielectric layer A, the lossy dielectric layer B and the lossy dielectric layer C are solidified and combined through a fused deposition modeling process to obtain a three-layer absorbing structure.

[0016] The mass fraction of carbonyl iron in the lossy dielectric layer A is 40%~70%, and the mass fraction of polylactic acid is 30%~60%; preferably, the mass fraction of carbonyl iron in the lossy dielectric layer A is 40%~60%, and the mass fraction of polylactic acid is 40%~60%; more preferably, the mass fraction of carbonyl iron in the lossy dielectric layer A is 55%~60%, and the mass fraction of polylactic acid is 40%~45%.

[0017] The mass fraction of nanographite in the lossy dielectric layer B is 10% to 30%, and the mass fraction of polylactic acid is 70% to 90%; preferably, the mass fraction of nanographite in the lossy dielectric layer B is 10% to 20%, and the mass fraction of polylactic acid is 80% to 90%; more preferably, the mass fraction of nanographite in the lossy dielectric layer B is 10% to 15%, and the mass fraction of polylactic acid is 85% to 90%.

[0018] The mass fraction of the nano-carbon particles in the lossy dielectric layer C is 10%~30%, and the mass fraction of the polylactic acid is 70%~90%; preferably, the mass fraction of the nano-carbon particles in the lossy dielectric layer C is 10%~20%, and the mass fraction of the polylactic acid is 80%~90%; more preferably, the mass fraction of the nano-carbon particles in the lossy dielectric layer C is 15%~20%, and the mass fraction of the polylactic acid is 85%~90%.

[0019] The thickness of the three-layer absorbing structure is 3-5 mm, the thickness of the lossy dielectric layer A is 1-3 mm, the thickness of the lossy dielectric layer B is 1-3 mm, and the thickness of the lossy dielectric layer C is 1-3 mm; preferably, the thickness of the lossy dielectric layer A is 1-2 mm, the thickness of the lossy dielectric layer B is 1-2 mm, and the thickness of the lossy dielectric layer C is 2-4 mm. More preferably, the thickness of the lossy dielectric layer A is less than the thickness of the lossy dielectric layer C.

[0020] The three-layer absorbing structure composed of lossy dielectric layer A, lossy dielectric layer B and lossy dielectric layer C is adopted. Through the lamination design of absorbing materials, the effective absorbing frequency band can be expanded. However, since the wave impedance matching of the material interface is not optimal, the absorbing performance in the mid-frequency band cannot reach the expected effect. The electromagnetic loss performance of the three-layer absorbing material of the present invention is better than that of the double-layer absorbing material. The added intermediate dielectric loss layer plays a transitional role in wave impedance, making the wave impedance reasonably gradual and broadening the effective absorbing bandwidth. The reflection loss value in the mid-frequency band is better than that of the double-layer absorbing material. The design of the three-layer structure can improve the electromagnetic loss performance in the mid-frequency band.

[0021] The working principle of the three-layer structure of the present invention is: from the surface of the lossy dielectric layer A to the interface between the lossy dielectric layers, the wave impedance decreases successively, and the wave impedance on the surface of the structure is close to the wave impedance of free space, so that most of the electromagnetic waves enter the interior of the material. The added intermediate dielectric loss layer plays a transitional role in the wave impedance, making the wave impedance reasonably gradual and broadening the effective wave absorption bandwidth. The reflection loss value in the mid-frequency band is better than that of the double-layer absorbing material. The design of the three-layer structure can improve the electromagnetic loss performance in the mid-frequency band.

[0022] The present invention also provides a method for preparing a three-layer absorbing structure, comprising the following steps: (1) Using carbonyl iron and polylactic acid to prepare a carbonyl iron polylactic acid composite material comprises the following steps: S1, drying carbonyl iron and polylactic acid powder in an oven at 80-100°C for at least 12 h; S2, dispersing the proportional mixture of carbonyl iron and polylactic acid in a planetary mixer at a speed of 60-100 r / min for at least 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into a single screw extruder, the composite particles are heated and melted in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the composite wire is obtained by the dual action of water tank cooling and traction sizing, such as a 1.75 diameter 0.05 mm composite wire.

[0023] (2) Using nano-graphite and polylactic acid to prepare a nano-graphite polylactic acid composite material, comprising the following steps: S1, drying the nanographite and polylactic acid powder in an oven at 80 °C for at least 12 h; S2, dispersing the proportion of nanographite and polylactic acid in a planetary mixer at a speed of 60-100 r / min for at least 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into a single screw extruder, the composite particles are heated and melted in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the composite wire with a diameter of 1.75 mm is obtained under the dual action of water tank cooling and traction sizing. 0.05 mm composite wire.

[0024] (3) Using nano-carbon particles and polylactic acid to prepare a nano-carbon particle polylactic acid composite material comprises the following steps: S1, drying the nanocarbon particles and polylactic acid powder in an oven at 80-100 °C for at least 12 h; S2, dispersing the proportion of nanocarbon particles and polylactic acid in a planetary mixer at a speed of 60-100 r / min for at least 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into a single screw extruder, the composite particles are heated and melted in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the composite wire is obtained by the dual action of water tank cooling and traction sizing, such as a 1.75 diameter 0.05 mm composite wire.

[0025] (4) Using nano-carbon particle polylactic acid composite wire, a lossy dielectric layer C is formed by a fused deposition molding process; on the lossy dielectric layer C, a nano-graphite polylactic acid composite wire is used to form a lossy dielectric layer B by a fused deposition molding process; on the lossy dielectric layer B, a carbonyl iron polylactic acid composite wire is used to form a lossy dielectric layer A by a fused deposition molding process, thereby obtaining a three-layer absorbing structure. The optimal printing temperature of the composite wire is 200~230℃, and the printing speed is 30~40 mm / s.

[0026] The effective absorbing bandwidth (reflection loss less than -10 dB) of the lossy dielectric layer A and lossy dielectric layer B prepared by the present invention at a matching thickness of 3 mm is significantly better than that of the absorbing composite wire in the literature, and has stronger electromagnetic loss performance. This is due to the two-step melt blending preparation process, which significantly improves the mass ratio and dispersibility of the absorbent, and realizes the preparation of the absorbing composite wire with high electromagnetic loss performance.

[0027] Table 1 Comparison of the performance of the microwave absorbing composite wires reported in the literature and prepared by the present invention

[0028] Note: CI-60 / PLA means that the mass content of carbonyl iron is 60%, and the rest is the matrix material PLA; NGP-10 / PLA means that the mass content of nanographite is 10%, and the rest is the matrix material PLA; NPC-20 / PLA means that the mass content of nanocarbon particles is 20%, and the rest is the matrix material PLA.

[0029] [1] Hu Zhenglang, Wu Haihua, Yang Zenghui, et al. Preparation and microwave absorption properties of graphene-iron-nickel alloy-polylactic acid composites. Journal of Composite Materials, 2022, 39: 1-14.

[0030] [2] Ye Xicong, Yang Chao, Ouyang Bin, et al. Graphene enhanced microwave absorption properties of FeSiAl-MoS2 / PLA composites. Journal of Composite Materials, 2023, 40(2): 911-928.

[0031] [3]Duan Y, Liang Q, Yang Z, et al. A wide-angle broadband electromagnetic absorbing metastructure using 3D printing technology. Materials&Design, 2021, 208: 109900. [4] Ye Xicong, Ouyang Bin, Yang Chao, et al. Preparation of graphene-carbonyl iron powder wire and analysis of its microwave absorption performance. Journal of Composite Materials, 2021, 39: 1-12.

[0032] Example Example 1 Embodiment 1 provides a method for preparing a three-layer absorbing structure, which comprises the following steps: (1) Using carbonyl iron and polylactic acid to prepare a carbonyl iron polylactic acid composite material comprises the following steps: S1, drying carbonyl iron and polylactic acid powder in an oven at 80 °C for 12 h; S2, a mixture of carbonyl iron and polylactic acid with a mass ratio of 6:4 was dispersed in a planetary mixer at a speed of 60 r / min for 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into the single screw extruder, the composite particles are melted by heat in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the diameter of the 1.75 mm diameter is obtained by the dual action of water tank cooling and traction sizing. 0.05 mm composite wire CI-60 / PLA.

[0033] (2) Using nano-carbon particles and polylactic acid to prepare a nano-carbon particle polylactic acid composite material comprises the following steps: S1, drying the nanocarbon particles and polylactic acid powder in an oven at 80 °C for 12 h; S2, a mixture of nano-graphite particles and polylactic acid with a mass ratio of 1:9 was dispersed in a planetary mixer at a speed of 60 r / min for 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into the single screw extruder, the composite particles are melted by heat in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the diameter of the 1.75 mm diameter is obtained by the dual action of water tank cooling and traction sizing. 0.05 mm composite wire NGP-10 / PLA.

[0034] (3) Using nano-carbon particles and polylactic acid to prepare a nano-carbon particle polylactic acid composite material comprises the following steps: S1, drying the nanocarbon particles and polylactic acid powder in an oven at 80 °C for 12 h; S2, a mixture of nanocarbon particles and polylactic acid with a mass ratio of 2:8 was dispersed in a planetary mixer at a speed of 60 r / min for 8 h; S3, melting and mixing the mixture and extruding it through a pelletizer to form composite pellets; S4, pour the dried composite material particles into the single screw extruder, the composite particles are melted by heat in the screw, and further mixed under the action of screw friction and shear. The molten mixture is extruded from the die, and the diameter of the 1.75 mm diameter is obtained by the dual action of water tank cooling and traction sizing. 0.05 mm composite wire NPC-20 / PLA.

[0035] (4) Using nano-carbon particle polylactic acid absorbing composite wire, the lossy dielectric layer C is formed by the fused deposition molding process; on the lossy dielectric layer C, the nano-graphite polylactic acid composite wire is used to form the lossy dielectric layer B by the fused deposition molding process; on the lossy dielectric layer B, the carbonyl iron polylactic acid composite wire is used to form the lossy dielectric layer A by the fused deposition molding process, and a three-layer absorbing structure CI-60-1mm / NGP-10-1mm / NPC-20-3mm is obtained. The optimal printing temperature of the composite wire is 230℃ and the printing speed is 40 mm / s.

[0036] The three-layer absorbing structure CI-60-1mm / NGP-10-1mm / NPC-20-3mm has lossy dielectric layer A (CI-60 / PLA) as the surface layer with a thickness of 1mm; lossy dielectric layer B (NGP-10 / PLA) as the middle layer with a thickness of 1mm; lossy dielectric layer C (NPC-20 / PLA) as the bottom layer with a thickness of 3mm. The total thickness of the three-layer absorbing structure is 5mm.

[0037] For the design of three-layer materials, CI-60 / PLA is used as the surface layer of the three-layer absorbing material (thickness 1 mm), NGP-10 / PLA is used as the middle layer of the three-layer absorbing material (thickness 1 mm), and NPC-20 / PLA is used as the bottom layer of the three-layer absorbing material (thickness 3 mm). The surface reflection loss and interface wave impedance of the three-layer structure change with frequency as shown in the figure. Figure 2 As shown in the figure, there are two absorption peaks in the frequency range, and the corresponding reflection loss values ​​are -16.7 dB (5.6 GHz) and -32.3dB (16.7 GHz), and the effective absorption bands are 4.7-7.2 GHz and 14.3-18 GHz. The reflection loss values ​​in the 7.2-14.3 GHz band are all less than -6.6 dB, which has a certain electromagnetic loss capacity and is evenly distributed. Figure 2 , surfacelayer is the surface layer, interface layer 01 is the interface layer between the surface layer and the middle layer, and interface layer 02 is the interface layer between the middle layer and the bottom layer.

[0038] From the wave impedance model, it can be seen that in the 2.6-6.8 GHz and 12.9-18.0 GHz frequency bands, the surface wave impedance is greater than the interface wave impedance, which is consistent with the gradual change of wave impedance. Therefore, the effective absorption frequency band where the two absorption peaks are located is within these two frequency bands. In the 6.8-12.9 GHz frequency band, the surface wave impedance is less than the interface wave impedance, but the difference is not large, which will only cause a small part of the electromagnetic waves to be reflected.

[0039] Example 2 Example 2 The preparation method in Example 1 is used to form a three-layer absorbing structure CI-60-1mm / NGP-10-2mm / NPC-20-2mm, with lossy dielectric layer A (CI-60 / PLA) as the surface layer, with a thickness of 1mm; lossy dielectric layer B (NGP-10 / PLA) as the middle layer, with a thickness of 2mm; lossy dielectric layer C (NPC-20 / PLA) as the bottom layer, with a thickness of 2mm. The total thickness of the three-layer absorbing structure is 5mm.

[0040] The surface reflection loss and interface wave impedance of the three-layer structure vary with frequency. Figure 3 As shown in the figure, there are two absorption peaks in the frequency range, and the corresponding reflection loss values ​​are -10.7 dB (6.1 GHz) and -24.1 dB (17.2 GHz), and the effective absorption bands are 5.7-6.6 GHz and 15.3-18 GHz, respectively. The reflection loss values ​​in the 7.2-14.3 GHz frequency band are all less than -5.7 dB, which has a certain electromagnetic loss capacity. Figure 3 In the figure, surface layer is the surface layer, interfacelayer 01 is the interface layer between the surface layer and the middle layer, and interface layer 02 is the interface layer between the middle layer and the bottom layer.

[0041] From the wave impedance model, it can be seen that in the 2.6-6.3 GHz and 16.2-18.0 GHz frequency bands, the surface wave impedance is greater than the interface wave impedance, which is consistent with the gradual change of wave impedance. Therefore, the effective absorption frequency band where the two absorption peaks are located is within the range of these two frequency bands. In the 6.3-16.2 GHz frequency band, the surface wave impedance is less than the interface wave impedance, and the difference is small, which will only cause a small part of the electromagnetic waves to be reflected.

[0042] Comparative Example 1 Comparative Example 1 is consistent with Example 1, except that a double-layer absorbing structure CI-60-1mm / NPC-20-4mm is prepared, wherein the lossy dielectric layer A (CI-60 / PLA) is the surface layer with a thickness of 1mm; and the lossy dielectric layer B (NPC-20 / PLA) is the bottom layer with a thickness of 4mm; the total thickness of the double-layer absorbing structure is 5mm.

[0043] Comparative Example 1 uses CI-60 / PLA as the surface layer (thickness 1 mm) of the double-layer absorbing material, and uses NPC-20 / PLA as the bottom layer (thickness 4 mm) of the double-layer absorbing material. The curves of the surface reflection loss and interface wave impedance of the double-layer structure with frequency are shown in Figure 1. Figure 4As shown in the figure, there are two absorption peaks in the frequency range, and the corresponding reflection loss values ​​are -36.9 dB (4.8 GHz) and -23.2 dB (16.7 GHz), respectively. The effective absorption bands are 3.8-6.4 GHz and 14.9-18 GHz, respectively. The reflection loss values ​​in the 6.4-14.9 GHz band are all less than -5.8 dB, which has a certain electromagnetic loss capacity and is evenly distributed. From the wave impedance mode, it can be seen that in the 2.6-5.5 GHz and 10.4-18 GHz bands, the surface wave impedance is greater than the interface wave impedance, which conforms to the gradual change of wave impedance. Therefore, the effective absorption bands where the two absorption peaks are located are within the range of these two frequency bands.

[0044] Comparing the electromagnetic loss performance of Example 1 with that of Comparative Example 1, the effective absorbing bandwidth of Example 1 is better than that of Comparative Example 1. The three-layer absorbing material design with an added intermediate layer makes the wave impedance reasonably gradual, and the intermediate layer plays a transitional role in the wave impedance, which improves the electromagnetic loss performance in the mid-frequency band, and the reflection loss values ​​are all less than -6.6 dB. The present invention is described in detail above in conjunction with specific implementation methods and exemplary examples, but these descriptions cannot be understood as limitations on the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution and implementation methods of the present invention, which all fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0045] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.

Claims

1. A three-layer absorbing structure, characterized in that: including a lossy dielectric layer A, a lossy dielectric layer B and a lossy dielectric layer C; The lossy dielectric layer A is used as the surface layer, the base material is polylactic acid, and the filler is spherical carbonyl iron; The lossy dielectric layer B is used as the middle layer, the base material is polylactic acid, and the filler is nanographite; The lossy dielectric layer C is used as the bottom layer, the matrix material is polylactic acid, and the filler is nano-carbon particles.

2. The three-layer absorbing structure according to claim 1, characterized in that: The mass fraction of carbonyl iron in the lossy dielectric layer A is 40% to 70%, and the mass fraction of polylactic acid is 30% to 60%.

3. The three-layer absorbing structure according to claim 1, characterized in that: The mass fraction of nanographite in the lossy dielectric layer B is 10% to 30%, and the mass fraction of polylactic acid is 70% to 90%.

4. The three-layer absorbing structure according to claim 1, characterized in that: The mass fraction of the nano-carbon particles in the lossy dielectric layer C is 10% to 30%, and the mass fraction of the polylactic acid is 70% to 90%.

5. The three-layer absorbing structure according to claim 1, characterized in that: The thickness of the three-layer absorbing structure is 3-5 mm, the thickness of the lossy dielectric layer A is 1-3 mm, the thickness of the lossy dielectric layer B is 1-3 mm, and the thickness of the lossy dielectric layer C is 1-3 mm.

6. A method for preparing a three-layer absorbing structure according to any one of claims 1 to 5, characterized in that: The steps include: Carbonyl iron and polylactic acid are used to prepare carbonyl iron polylactic acid composite wire; Nano-graphite and polylactic acid are used to prepare nano-graphite polylactic acid composite wires; Nanocarbon particles and polylactic acid are used to prepare nanocarbon particle polylactic acid composite wires; The lossy dielectric layer C is formed by using nano-carbon particle polylactic acid composite wire through a fused deposition molding process; On the lossy dielectric layer C, nano-graphite polylactic acid composite wire is used to form the lossy dielectric layer B through a fused deposition molding process; on the lossy dielectric layer B, carbonyl iron polylactic acid composite wire is used to form the lossy dielectric layer A through a fused deposition molding process, thereby obtaining a three-layer absorbing structure.

7. The method for preparing a three-layer absorbing structure according to claim 6, characterized in that: The step of preparing the carbonyl iron-polylactic acid composite wire by using carbonyl iron and polylactic acid comprises: drying carbonyl iron and polylactic acid powder; The proportioned mixture of carbonyl iron and polylactic acid is fully dispersed in a planetary mixer; The mixture is melted, mixed and extruded through a pelletizer to form composite pellets; The dried composite material particles are poured into a screw extruder, and the molten mixture is extruded from a die, and composite wires are obtained through the dual effects of cooling and traction sizing.

8. The method for preparing a three-layer absorbing structure according to claim 6, characterized in that: The step of preparing the nano-graphite polylactic acid composite wire by using nano-graphite and polylactic acid comprises: Drying the nano-graphite and polylactic acid powder; The proportioned mixture of nanographite and polylactic acid is fully dispersed in a planetary mixer; The mixture is melted, mixed and extruded through a pelletizer to form composite pellets; The dried composite material particles are poured into a screw extruder, and the molten mixture is extruded from a die, and composite wires are obtained through the dual effects of cooling and traction sizing.

9. The method for preparing a three-layer absorbing structure according to claim 6, characterized in that: The step of using nano-carbon particles and polylactic acid to prepare a nano-carbon particle polylactic acid composite wire comprises: drying the nanocarbon particles and the polylactic acid powder; The proportioned mixture of nanocarbon particles and polylactic acid is fully dispersed in a planetary mixer; The mixture is melted, mixed and extruded through a pelletizer to form composite pellets; The dried composite material particles are poured into a screw extruder, and the molten mixture is extruded from a die, and composite wires are obtained through the dual effects of cooling and traction sizing.

10. The method for preparing a three-layer absorbing structure according to claim 6, characterized in that: When the lossy dielectric layer A, the lossy dielectric layer B and the lossy dielectric layer C are formed by the fused deposition modeling process, the printing temperature of the composite wire is 200-230°C and the printing speed is 30-40 mm / s.

Citation Information

Patent Citations

  • Wave absorbing composite material and preparation method thereof

    CN109843029A

  • Ultra-wideband wave-absorbing material and preparation method thereof

    CN113161761A

  • Wave-absorbing composite material as well as preparation method and application thereof

    CN118027660A